Study the Prevalence of Giardia Parasite and the Relationship of Some Living and Haematological Variables to Infection - Noor Thamer Ghafori; Thaer Abdulqader Salih (Indian Journal of Forensic Medicine & Toxicology, 2021)
During the period from 10th September into 31th December-2020 study has done.. Eighty five (85) stoolsamples had collected from(33) females and (52) males from different age group (1-55) years among patientssuffering from gastrointestinal disturbances who attending to various governmental hospitals (FallujahGeneral Hospital, Teaching laboratory and Consultant clinic) in Fallujah City with the main clinical features(abdominal pain, nausea, bloating , heart burn and loss of appetite), And some of them did not suffer fromany pathological symptoms (control) , 25 samples were infected with Giardia, 25 samples were uninfected(control), and 25 samples were infected with other secondary infections.The results showed that males are more likely than females to be infected, and that age greater than 10 yearswas the most affected age group, and the rate of infection in urban was slightly higher than in the rural , Theresults also showed a significant increase in the rate of white blood cells, unlike the rest of the other bloodfactors (Hb, PCV, PLT, RBC), which had no significant differences, and the blood factors for some of themhad a correlation with age, sex, living status, and other factors that did not Have no affiliation .